Face‐to‐face interviews versus Internet surveys: Comparison of two data collection methods in the Rome foundation global epidemiology study: Implications for population‐based research. Issue 6 (5th April 2023) - Sperber, Ami D.; Bor, Serhat; Fang, Xuicai; Bangdiwala, Shrikant I.; Drossman, Douglas A.; Ghoshal, Uday C.; Simren, Magnus; Tack, Jan; Whitehead, William E.; Dumitrascu, Dan L.; Fukudo, Shin; Kellow, John; et al.
Abstract: Background and Aims: The Rome Foundation Global Epidemiology Study (RFGES) assessed the prevalence, burden, and associated factors of Disorders of Gut–Brain Interaction (DGBI) in 33 countries around the world. Achieving worldwide sampling necessitated use of two different surveying methods: In‐person household interviews (9 countries) and Internet surveys (26 countries). Two countries, China and Turkey, were surveyed with both methods. This paper examines the differences in the survey results with the two methods, as well as likely reasons for those differences. Methods: The two RFGES survey methods are described in detail, and differences in DGBI findings summarized for household versus Internet surveys globally, and in more detail for China and Turkey. Logistic regression analysis was used to elucidate factors contributing to these differences. Results: Overall, DGBI were only half as prevalent when assessed with household vs Internet surveys. Similar patterns of methodology‐related DGBI differences were seen within both China and Turkey, but prevalence differences between the survey methods were dramatically larger in Turkey. No clear reasons for outcome differences by survey method were identified, although greater relative reduction in bowel and anorectal versus upper gastrointestinal disorders when household versus Internet surveying was used suggests an inhibiting influence of social sensitivity. Conclusions: The findings strongly indicate that besides affecting data quality, manpower needs and data collection time and costs, the choice of survey method is a substantial determinant of symptom reporting and DGBI prevalence outcomes. This has important implications for future DGBI research and epidemiological research more broadly. Abstract : The Rome Foundation Global Epidemiology Study assessed the prevalence, burden and associated factors of Disorders of Gut–Brain Interaction in 33 countries. Achieving worldwide sampling necessitated use of two different surveying methods: in‐person household interviews (9 countries) and Internet surveys (26 countries). Two countries, China and Turkey, were surveyed with both methods. This paper examines the differences in the survey results with the two methods, as well as likely reasons for those differences.